Collaborative learning to promote values at El Sabanal School (2023)
This report describes the internship process conducted in the program Bilingualism for peace at El Sabanal school. This process was conducted in low elementary, second level belonging to the program and consisted of face-to-face and virtual classes. The principal purpose of this internship was to develop the importance of teamwork through games and didactic activities, provide them with the necessary accompaniment through the process and establish good relationships between classmates. In addition, it explains the essential pedagogical perspectives on which this paper is based, which are Collaborative learning (CL) and the role of play and games in child development. Finally, this internship reports discusses the methodologies, results, conclusions, recommendations, and limitations of this meaningful process for personal and professional growth.